Tailored peptide nanomaterials for receptor targeted prostate cancer imaging - (:unkn) unknown (Royal Society of Chemistry (RSC), 2024)
We report the development of a peptide-based optical nanoprobe specifically tailored for prostate cancer imaging. The imaging probe is comprised of cyclic peptide nanotubes, formed via the aqueous co-assembly of four cyclic D,L-alternating octapeptides. ...
Keywords: Nanomateriales peptídicos; Cáncer de próstata